Systematic Review of the Underlying Factors of Consensual Divorce of Couples in the last Decade in Iran (2009-2020) - loghman ebrahimi; maryam MohammadLou (فصلنامه زن و جامعه, 2021)
The present study aimed to identify the underlying factors of consensual divorce through a systematic review. Document analysis method was used to collect data. The study population included all published quantitative and qualitative researches (2009-2020) and a total of 192 quantitative and qualitative researches were examined and from this number, 56 researches were selected as the sample size. The obtained information was made by the researcher checklist tool and the summary was presented in the form of tables. Findings showed: Three categories of factors play a role as the basis of consensual divorce as individual, interpersonal and extra-individual, so that in the individual dimensions, the factors of personality and psychological characteristics (mental illness, eye and eye, beating, lying, respectively) Suspicion and pessimism, betrayal, moral and behavioral violence, impatience and forgiveness, positive image of the consequences of divorce, source of control and resilience, couple idealism), addiction, sexual relations, religious beliefs, education; In the interpersonal dimension, respectively, the factor of weakness in communication skills, family factors, interference of others, premarital relationships, and in the interpersonal dimension, respectively, factors related to culture (hasty acquaintance and cognition, lack of appropriate premarital education, respectively). Cultural and class differences, forced marriage, polygamy, economic factors (unemployment, low income, unsustainable employment, earning money the wrong way, lack of housing and debt), satellite and virtual networks, social factors (social status, lack of social skills, Negative attitudes toward women's housekeeping (emotional relationships with the opposite sex) and lifestyle (industrialization and urbanization)